Tumor-like characteristics of vascular smooth muscle cells in atherosclerosis - Li, Xiangchun; Deng, Yuyan (Frontiers in Pharmacology, 2026)
Atherosclerosis is a complex, chronic inflammatory disease, traditionally considered a lipid-driven and immune-mediated disorder whose pathogenesis involves the interplay of multiple cellular populations. Vascular smooth muscle cells (SMCs) have long been considered contractile and extracellular matrix-producing cells that stabilize the fibrous cap. However, recent advances in lineage tracing and single-cell transcriptomics have revealed that vascular SMCs possess a high degree of plasticity and exhibit tumor-like characteristics during atherogenesis. Vascular SMCs and vascular smooth muscle cell-derived cells (SDCs) in atherogenesis exhibit DNA damage and genomic instability, evade senescence, hyperproliferate, activation of migration and invasion, cancer stem cell-like property, and activate multiple cancer-related signaling pathways. These tumor-like behaviors accelerate phenotypic switching of vascular SMCs and lesion progression. In this review, we mainly discuss the tumor-like characteristics of vascular SMCs, aiming to provide a theoretical basis for new therapeutic strategies targeting vascular SMCs and provide new ideas for the precise prevention and treatment of atherosclerosis.